Monitoramento e modelagem hidrológica da bacia hidrográfica do rio Siriri Vivo-SE - Cruz, Sandro Iury Valverde Lima da (2012)
Water is a valuable and limited natural resources, since it is the basis for the existence of life and economic development. The uneven distribution of water through different regions, causes the shortage of the resource in various locations, both at the local, regional or global. Aggravating even more the situation, the misuse of this feature is causing serious problems for communities that suffer from the reduction of quantity and quality of water resources. These problems are caused mainly by human activities, such as the expansion of urbanization that waterproofs the soil interfering with the hydrological cycle, the removal of riparian vegetation for the practice of pastoral and agricultural activities. Therefore, it is necessary to carry out studies to understand the behavior of these sources. The hydrological modeling is one of the tools that science has developed to better understand and represent the behavior of a watershed and provide conditions different from those observed. A hydrologic model can be considered as a simplified representation of reality, aiding the understanding of processes involved in this reality. In this context, this paper aims to simulate the production of water in the river basin Siriri Vivo through the SWAT hydrologic model to see what the environmental conditions that influence this variável.A approach developed in this paper shows that the environmental analysis for system geographic information and the hydrological model SWAT allowed an integrated analysis and visualization of phenomena in geographic space.